Գործնական ու տեսական դաստիարակության մասին պարոնյանական դիտարկումները - Լուսյա Հարությունյան (ՀՀ ԳԱԱ հրատ.)
В наследии популярного сатирика А. Пароняна (1843-1891) можно найти оригинальные эпизоды о методах обучения, про армянскую школу, об учебниках и про учителей, что позволяет понять литературно-социальную деятельность педагога. The famous satirist Hagop Paronian’s literary heritage also includes distinguishing observations on the Armenian educational institutions, teaching methods, textbooks and teachers. All these allow getting an opinion about Paronian’s views on different literary and social activities as a pedagogue.
Keywords: Theory and practice of education